PULSED ELECTROMAGNETIC FIELDS SYNERGIZE WITH GRAPHENE TO ENHANCE DENTAL PULP STEM CELL-DERIVED NEUROGENESIS BY SELECTIVELY TARGETING TRPC1 CHANNELS - Madanagopal, TT (AO RESEARCH INSTITUTE DAVOS-ARI, 2021)
10.22203/eCM.v041a16